2019
DOI: 10.1002/adma.201808242
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Thermally Activated Delayed Fluorescence via J‐Aggregates with Strong Intermolecular Charge Transfer

Abstract: The development of high‐efficiency and low‐cost organic emissive materials and devices is intrinsically limited by the energy‐gap law and spin statistics, especially in the near‐infrared (NIR) region. A novel design strategy is reported for realizing highly efficient thermally activated delayed fluorescence (TADF) materials via J‐aggregates with strong intermolecular charge transfer (CT). Two organic donor–acceptor molecules with strong and planar acceptor are designed and synthesized, which can readily form J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
278
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(289 citation statements)
references
References 38 publications
10
278
1
Order By: Relevance
“…The nonradiative decay rate generally increases exponentially as the optical energy gap decrease. [18] Thus, the small HOMO-LOMO energy gap promotes the photothermal effect.…”
Section: Doi: 101002/adma201907855mentioning
confidence: 99%
See 1 more Smart Citation
“…The nonradiative decay rate generally increases exponentially as the optical energy gap decrease. [18] Thus, the small HOMO-LOMO energy gap promotes the photothermal effect.…”
Section: Doi: 101002/adma201907855mentioning
confidence: 99%
“…As a result, tfm‐BDP demonstrated a HOMO‐LUMO gap of 1.565 eV, smaller than H‐BDP (1.911 eV) and m‐BDP (1.835 eV), which was consistent with the bathochromic shift of tfm‐BDP seen experimentally. The nonradiative decay rate generally increases exponentially as the optical energy gap decrease 18. Thus, the small HOMO‐LOMO energy gap promotes the photothermal effect.…”
mentioning
confidence: 99%
“…[ 47 ] Note that the energy splitting for singlet and triplet excitons are dominated by Coulombic and exchange terms, respectively, [ 48 ] we envisage that the Δ E ST can be reduced without sacrificing f in dimers or aggregates. [ 49,50 ] As seen in Figure , for the V‐type and J‐type dimers formed by π−π stacking between the end‐groups, the triplet energy splitting is negligible due to the small intermolecular overlap; however, the singlet energy splitting can be very significant, and the lower‐energy state or both splitting states are dipole‐allowed. Consequently, the Δ E ST can be substantially reduced.…”
Section: Figurementioning
confidence: 99%
“…[ 11–14 ] Red TADF emitters with main emission peaks of above 600 nm, however, significantly underperform their blue and green counterparts in terms of both EQEs and PEs. [ 15–19 ] Up to date, there are only few reports on red TADF emitters having over 20% EQEs and above 30 lm W −1 PE, [ 20–25 ] and simultaneously achieving about 30% EQE and 50 lm W −1 PE for red TADF OLEDs is still a formidable challenge for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Red TADF emitters generally suffer more significant nonradiative processes (dominated by the nonradiative internal conversion) between S 1 and the ground state ( S 0 ), largely due to vibrational overlap between the zero‐vibrational levels of S 1 and the higher‐vibrational levels of S 0 governed by the energy gap law. [ 31 ] Accordingly, most of red TADF emitters have less than 70% Φ PL s. [ 16–20 ] To address this issue, ultrahigh molecular rigidity is highly required in constructing excellent red TADF emitters to suppress detrimental internal conversion processes. To illustrate, very recently Liao et al reported an efficient red TADF OLED with a high EQE of 28.1% and an electroluminescence (EL) emission peak at 648 nm using a dibenzo[a,c]phenazine‐3,6‐dicarbonitrile‐based red TADF emitter having nearly 100% Φ PL .…”
Section: Introductionmentioning
confidence: 99%